Indonesian Authors in Geneeskundige Tijdschrift voor Nederlands Indie as Constructors of Medical Science - Wahyu Suri Yani (Lembaran Sejarah, 2020)
Access to the publication Geneeskundig Tijdschrift voor Nederlandsch-Indië (GTNI), a Dutch Indies medical journal, was limited to European doctors. Although Stovia (School ter Opleiding van Inlandsche Artsen) was established to produce indigenous (Bumiputra) doctors, its students and graduates were not given access to GTNI. In response, educators at Stovia founded the Tijdschrift Voor Inlandsche Geneeskundigen (TVIG) as a special journal for indigenous doctors. Due to limited funds, TVIG – the only scientific medical publication for indigenous doctors – ceased publication in 1922. The physicians formed Vereeniging van Inlandsche Geneeskundigen (VIG) an association for pribumi (native) doctors to express various demands for equal rights, one of which was the right to access GTNI. The protests and demands of the bumiputra doctors resulted not only in being granted reading access rights but also being able to become writers for GTNI. Bumiputra doctors who contributed to GTNI included Bahder Djohan and Johannes Leimena. However, they were not the only authors who contributed to GTNI during the Dutch East Indies era. After Indonesia became independent, both doctors played major roles in laying the foundation for Indonesia’s health education system and implementing village-based health policies. This article is part of a research project on Indonesia’s health history using the archives of the GTNI, TVIG and books written by doctors who contributed to GTNI which were published from the early twentieth century onwards. This paper reconstructs the role of GTNI writers in building Indonesian health knowledge.